Heidi - Spyri, Johanna, 1827-1901; New Editions ([Hellinikon, Greece] : New Editions, 2006)
An orphan sent to live with her grandfather learns to love both the old man and the Swiss Alps
Level 1
Title from container
Keywords: Mountain life -- Fiction; Alps -- Fiction; Children's stories